Non-financial reporting and reputational risk in the Romanian financial sector - Laurenţiu Tăchiciu; Melinda Timea Fülöp; Andreea Marin-Pantelescu; Ionica Oncioiu; Dan Ioan Topor (Amfiteatru Economic Journal, 2020)
Good reputation is an important intangible asset for any company, but it can be vital for financial institutions. Today, given that the demands on the business environment in terms of social responsibility have greatly increased, the reputation can be worn not only by serious events, but also by the omission or delay of possible and necessary measures and actions to strengthen the sustainability of the activity. In this context, it turned out that there is a strong connection between reputational risk management and the public disclosure of information on the social and environmental impact of the company's activities. This paper proposes a contribution to the empirical decoding of this inter-conditioning through a two-pronged research: on one hand, it investigates the way in which Romanian banking institutions treat reputational risk management and, on the other hand, it analyzes the content of non-financial reports of some financial institutions in the light of the maturity with which they deal with sustainability. The resulting information suggests that there is a delay in understanding the significance of reputational risk and a decoupling of corporate responsibility policies from the risks associated with the business model.
Keywords: G21; M14; 330; reputational risk; social responsibility; non-financial reporting; financial sector